What are the cultural challenges that Risk Management Professionals face when working in Latin American companies with an implemented risk management framework? - Vélez Revilla, Abraham Jishar (2021)
While organizations are concerned about threats and uncertainty in their business objectives and goals; risks also represent rewards and opportunities. Risk attitudes are determined on individual, familiar, social, and corporate beliefs which are inherent, in the nature of the business and organizational culture that influ-ence risk management effectiveness. Risk management varies depending on the region where it is implemented, different variables come on stage as well as local laws and regulations. Companies face several challenges when it comes into aligning local poli-cies versus corporate guidelines. Employees from all levels must participate actively to learn and apply risk methodolo-gies and frameworks. Their success is not determined by either the type implemented nor the interactions among several departments, but by the level of maturity of the re-sources and tools in place. Latin America represents a singular case of analysis as its socio-economic reality in-fluences in the performance of international risk management practices and standards. This region also faces the challenges of making organizations aware of risk manage-ment practices to be less vulnerable and more profitable. Cultural behaviors within a country impact on the performance and acceptance of risk management practices in organizations established in Latin America. In this paper we will also discuss how Latin culture defines the tone of risk management best practices and outcomes within transnational companies which operate under different risk management frameworks.